Aplikasi Sistem Informasi Pengelolaan Paket Wisata (Studi Kasus SATU BIRU Travel) : - Erwin Suhandono; Ponco Sugiarto (Fakultas Teknik Universitas Pancasila, 2021)
This research is motivated by the lack of utilization of disseminating information on tour packages on SATU BIRU Travel which has not been computerized. These constraints can make it difficult for consumers to find information on tour packages that have been made. In this study, the data collection techniques used were observation, interviews and literature study. The method used to build this information system is the waterfall and object-oriented design using UML (Unified Modeling Language) and Black Box testing. The process in this study includes the process of managing tour packages, customer registration, customer status, financial income reports, implementation reports. The result of the research that will be implemented in the tour package management information system (the case study SATU BIRU Travel) is a system that can provide tour package information, customer registration, customer status, financial income reports, implementation reports, so that customers are expected to make it easier to order tour packages.